Age-related vulnerabilities along the hippocampal longitudinal axis - Ta, Anh Tuan (2013)
Evidence for an anterior-posterior gradient of age-related volume reduction along the hippocampal longitudinal axis has been reported in normal aging, but functional changes have yet to be systematically investigated. The current study applied an advanced brain mapping technique, large deformation diffeomorphic metric mapping (LDDMM), automatically delineating the hippocampus into the anterior and posterior segments based on anatomical landmarks. We studied this anterior-posterior gradient in terms of structural and functional MRI in 66 participants aged from 19 to 79 years. The results showed age-related structural volume reduction in both anterior and posterior hippocampi, with greater tendency for anterior decrease. FMRI task contrasts that robustly activated the anterior (associative/relational processing) and posterior (novelty) hippocampus independently, showed only significant reduction of activation in the anterior hippocampus as age increased. Our results revealed positive correlation between structural atrophy and functional decrease in the anterior hippocampi, regardless of task performance in normal aging. These findings suggest that anatomy and functions related to the anterior hippocampus may be more vulnerable to aging, than previously thought.